2022
DOI: 10.1158/0008-5472.can-21-2342
|View full text |Cite
|
Sign up to set email alerts
|

AMPK–mTOR–Mediated Activation of Autophagy Promotes Formation of Dormant Polyploid Giant Cancer Cells

Abstract: Dormant cancer cells that survive anti-cancer therapy can lead to cancer recurrence and disseminated metastases that prove fatal in most cases.Recently, specific dormant polyploid giant cancer cells (PGCC) have drawn our attention because of their association with the clinical risk of nasopharyngeal carcinoma (NPC) recurrence, as demonstrated by previous clinical data. In this study, we report the biological properties of PGCC, including mitochondrial alterations, and reveal that autophagy is a critical mechan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 51 publications
(80 reference statements)
0
38
0
Order By: Relevance
“…Update: In 2020 we reviewed the literature on the impact of PGCCs on therapy resistance and disease relapse [ 4 ]. Since then, significant progress has been made in this field, including the demonstrations that: increased cellular stiffness, therapy resistance and migratory persistence of PGCCs is driven in part by dysregulation of actin cytoskeletal organization [ 78 ]; hypoxia-induced PGCCs can promote malignancy and an immune-suppressive microenvironment [ 79 ]; autophagy plays a key role in the formation and fate of PGCCs [ 80 , 81 ]; and chemotherapy-induced temporary cell cycle arrest (premature senescence) in cancer cells with differing p53 status can be followed by polyploidization and reprogramming, leading to changes in the expression of genes involved in meiosis and spermatogenesis regulation, resulting in the emergence of descendants that appear to arise inside PGCCs [ 76 ]. There is also recent evidence that mutation in the SF3B1 gene can promote formation of PGCCs in the K562 leukemia cell line [ 82 ].…”
Section: Well Established and Yet Widely Overlooked Therapy-induced C...mentioning
confidence: 99%
See 1 more Smart Citation
“…Update: In 2020 we reviewed the literature on the impact of PGCCs on therapy resistance and disease relapse [ 4 ]. Since then, significant progress has been made in this field, including the demonstrations that: increased cellular stiffness, therapy resistance and migratory persistence of PGCCs is driven in part by dysregulation of actin cytoskeletal organization [ 78 ]; hypoxia-induced PGCCs can promote malignancy and an immune-suppressive microenvironment [ 79 ]; autophagy plays a key role in the formation and fate of PGCCs [ 80 , 81 ]; and chemotherapy-induced temporary cell cycle arrest (premature senescence) in cancer cells with differing p53 status can be followed by polyploidization and reprogramming, leading to changes in the expression of genes involved in meiosis and spermatogenesis regulation, resulting in the emergence of descendants that appear to arise inside PGCCs [ 76 ]. There is also recent evidence that mutation in the SF3B1 gene can promote formation of PGCCs in the K562 leukemia cell line [ 82 ].…”
Section: Well Established and Yet Widely Overlooked Therapy-induced C...mentioning
confidence: 99%
“…There is also recent evidence that mutation in the SF3B1 gene can promote formation of PGCCs in the K562 leukemia cell line [ 82 ]. In addition to numerous research articles (e.g., [ 76 , 78 , 79 , 80 , 81 , 82 ]), in 2022, several comprehensive reviews were published that discussed different aspects of PGCCs in tumorigenesis and therapy resistance across different cancer types (e.g., [ 83 , 84 , 85 , 86 ]).…”
Section: Well Established and Yet Widely Overlooked Therapy-induced C...mentioning
confidence: 99%
“…However, we and others have demonstrated that PGCCs are viable and capable of generating mitotically active daughter cells via amitotic mechanisms [20][21][22][23]. PGCCs were shown to give rise to viable daughter cells following stresses induced by irradiation [21,24,25], chemotherapy [22,[26][27][28][29][30], a hypoxia-mimetic agent cobalt chloride (CoCl 2 ) [31], cellular or viral oncogene-induced senescence [32], and gene mutation in leukemia cells [33]. PGCCs have also been shown to express embryonic stemness markers [27,34].…”
Section: Introductionmentioning
confidence: 99%
“…Current studies have found that autophagy regulation involves a variety of signaling pathways, among which the adenosine monophosphate-activated protein kinase (AMPK) and mammalian target of rapamycin (mTOR) signaling pathways are the regulatory core. AMPK promotes autophagy, whereas mTOR inhibits autophagy [18][19][20]. In addition, many classical apoptotic signaling pathways and proteins have been found to be intricately intertwined with autophagy regulation [21][22][23].…”
Section: Discussionmentioning
confidence: 99%